Legal Regulation and the Role of Cross-Border Electronic Commerce in the Process of Post-War Reconstruction of Ukraine - Ustymenko, Volodymyr; Teremetskyi, Vladyslav; Kurepina, Olena; Nemyrovska, Oksana; Poltavskyy, Oleg; Dovhan, Viktor (Journal of Ecohumanism, 2024)
The article examines the role of e-commerce and commercial representation in the context of the post-war reconstruction of Ukraine. The theoretical and legal characterization of electronic commerce and e-business in Ukraine was carried out, and their legal nature was revealed. The regulation of e-commerce in European law is considered, and examples of legal regulation of cross-border e-commerce in EU countries are given. Special attention is paid to commercial representation as a form of electronic commerce and its role in the reconstruction of Ukraine. Electronic trust services as an important aspect of commercial mediation in Ukraine have been studied. The process of bringing Ukraine’s digital space closer to EU standards and its impact on the economy, in particular in the conditions of martial law, are analyzed. The potential of e-commerce to stimulate international business cooperation, cross-border operations, and diversification of sales markets abroad has been revealed. Challenges related to the process of convergence of Ukraine’s digital space with EU standards have been identified. A set of measures is proposed to maximize the positive impact of the development of electronic trust services and electronic commerce on the economy of Ukraine. A conclusion was made about the key role of the development of e-commerce in strengthening the economy, filling the budget, and deepening Ukraine’s international relations. The significance of these processes for ensuring the financing of investment projects for the reconstruction and integration of Ukraine into the European digital market is emphasized.